Sintered Steel Composites Reinforced with Ceramic Nanoparticles: Fabrication, Characteristics and Wear Behavior - Hassan Abdoos (Mechanics of Advanced Composite Structures)
Steel composites reinforced with alumina nanoparticles were prepared by powder metallurgy process. Samples containing two different amounts of carbon (0.35 and 0.55 wt.%) and 0-5 wt.% Al2O3 nanoparticles were fabricated by mixing, compacting and sintering of diffusion bonded Distaloy AE powder. The density, hardness and wear tests were performed on the prepared samples. Furthermore, the microstructures and worn surfaces were analyzed by optical and scanning electron microscope (SEM), respectively. The wear tests were carried out in forces of 30, 40 and 50 kN and 1000 m distance in dry condition and ambient temperature. The results showed that increasing the alumina nanoparticles would reduce the density (~ 10.8 and 9.6 % for 0.35 and 0.55 wt.% C, respectively) and would increase the hardness (~ 14.1 and 7.2 % for 0.35 and 0.55 wt.% C, respectively) of sintered samples. With increasing carbon content, the amount of lost material and the rate of wear decrease. The lost volume increases with increasing wear distance and applied force. Addition of reinforcement to the steel matrix, improves the wear resistance up to 3 wt.% alumina nanoparticles. This increase in the samples varies between 30% to 73%. More increasing of alumina (5 wt.%) decreases the wear resistant of samples. The wear mechanisms including oxidation in low forces that convert to adhesive and abrasive with increasing applied force. The wear curves indicate that as the wear distance increases, the lost volume increases, while the wear rate decreases.